IARSAF 20th annual symposium - award ceremony - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
The International Association of Research Scholars and Fellows (IARSAF) of IITA organizes her annual symposium which create opportunities for students to interact and exchange ideas on their research activities. The theme of this year’s symposium is “Contributions of IITA postgraduate students’ research for transforming African agriculture”. Towards this event, you are hereby invited to submit abstracts for both poster and oral presentations on your research work.